The Potential Role of the Intestinal Micromilieu and Individual Microbes in the Immunobiology of Chimeric Antigen Receptor T-Cell Therapy - Schubert, Maria-Luisa; Rohrbach, Roman; Schmitt, Michael; Stein-Thoeringer, Christoph K. (Frontiers in Immunology, 2021)
Cellular immunotherapy with chimeric antigen receptor (CAR)-T cells (CARTs) represents a breakthrough in the treatment of hematologic malignancies. CARTs are genetically engineered hybrid receptors that combine antigen-specificity of monoclonal antibodies with T cell function to direct patient-derived T cells to kill malignant cells expressing the target (tumor) antigen. CARTs have been introduced into clinical medicine as CD19-targeted CARTs for refractory and relapsed B cell malignancies. Despite high initial response rates, current CART therapies are limited by a long-term loss of antitumor efficacy, the occurrence of toxicities, and the lack of biomarkers for predicting therapy and toxicity outcomes. In the past decade, the gut microbiome of mammals has been extensively studied and evidence is accumulating that human health, apart from our own genome, largely depends on microbes that are living in and on the human body. The microbiome encompasses more than 1000 bacterial species who collectively encode a metagenome that guides multifaceted, bidirectional host-microbiome interactions, primarily through the action of microbial metabolites. Increasing knowledge has been accumulated on the role of the gut microbiome in T cell-driven anticancer immunotherapy. It has been shown that antibiotics, dietary components and gut microbes reciprocally affect the efficacy and toxicity of allogeneic hematopoietic cell transplantation (allo HCT) as the prototype of T cell-based immunotherapy for hematologic malignancies, and that microbiome diversity metrics can predict clinical outcomes of allo HCTs. In this review, we will provide a comprehensive overview of the principles of CD19-CART immunotherapy and major aspects of the gut microbiome and its modulators that impact antitumor T cell transfer therapies. We will outline i) the extrinsic and intrinsic variables that can contribute to the complex interaction of the gut microbiome and host in CART immunotherapy, including ii) antibiotic administration affecting loss of colonization resistance, expansion of pathobionts and disturbed mucosal and immunological homeostasis, and ii) the role of specific gut commensals and their microbial virulence factors in host immunity and inflammation. Although the role of the gut microbiome in CART immunotherapy has only been marginally explored so far, this review may open a new chapter and views on putative connections and mechanisms.